Analysis on the Root Crack Propagation Path and Its Influencing Factor of Spur Gear - Qikun Liu; Shengli Wu; Zhi Li; Xiaochun Jian (Jixie chuandong)
Under the action of alternating load，the gear is easy to generate fatigue crack fault in the tooth root，and the crack propagation will not only affect the transmission accuracy，but even cause serious safety accident and economic loss. Therefore，it is urgent to study the evolution law of tooth root crack propagation. For this，by using complex function method，the Westergaard stress function is constructed to analyze the complex stress field at the crack tip，and the critical condition of crack growth is determined according to the maximum circumferential tensile stress intensity factor theory. Considering the complexity of crack tip discontinuity and singularity in the process of crack propagation，the extended finite element method is modified and the finite element model of tooth root crack propagation is established to solve these problems. Study on the root crack nucleation point location and the crack propagation path of the relationship between the outside diameter of the web，the web hole and the corresponding location of the nucleation point in the gear matrix structure，the crack propagation law of different influencing factors is obtained and the accuracy and effectiveness of the modified finite element method is verified. The results greatly enrich the research on the evolutionary mechanism of tooth root fatigue crack propagation.